Pengaruh KIE tentang pemanfaatan buku KIA terhadap pengetahuan ibu hamil - Suhartini, Suhartini; Rosmiyati, Rosmiyati (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2023)
Background: The MCH book as a tool for early detection of disorders or problems of mother and child. The results of the survey revealed that as many as 8 (80%) revealed that so far health workers had never provided education or information related to the benefits of the MCH book for pregnancy. Purpose: Knowing communication, information, and education of utilization MCH books on pregnant mothers knowledge. Method: This type of quantitative research with a quasi-experimental research design. The research population of Trimester I pregnant women in the working area of ​​Tanjung Sari Health Center in Natar District, South Lampung Regency, a sample of 30 people, purposive sampling technique sampling. Analysis of univariate and bivariate t-test data. Results: There was influence after being given CIE has an increase in the level of knowledge by a difference of 10.13 points with p-value 0,000. Conclusion: There was communication, information, and education of utilization MCH books on pregnant mother’s knowledge. Keywords: CIE, MCH, Pregnant Mothers Knowledge Pendahuluan: Buku KIA sebagai alat untuk mendeteksi secara dini adanya gangguan atau masalah ibu dan anak. Hasil prasurvey diketahui bahwa sebanyak 8 (80%) mengungkapkan bahwa selama ini tenaga kesehatan (Bidan) tidak pernah memberikan pendidikan ataupun informasi terkait dengan manfaatnya buku KIA untuk kehamilan. Tujuan: Untuk mengetahui pengaruh KIE tentang pemanfaatan buku KIA terhadap pengetahuan ibu hamil. Metode: Jenis penelitian kuantitatif dengan rancangan penelitian quasi eksperimen. Populasi penelitian ibu hamil Trimester I di wilayah Kerja Puskesmas Tanjung Sari Kecamatan Natar Kabupaten Lampung Selatan berjumlah 113 ibu hamil, sampel sebanyak 30 orang, teknik sampling Purposive Sampling. Analisa data univariat dan bivariat uji t (t-test). Hasil: Ada pengaruh kelompok setelah diberikan KIE yang memiliki kenaikan tingkat pengetahuan dengan selisih 10,13 poin dan p–value 0,000. Simpulan: Ada pengaruh KIE tentang pemanfaatan buku KIA terhadap pengetahuan ibu hamil. Kata Kunci: KIE, KIA, Pengetahuan Ibu Hamil.